2015
DOI: 10.1371/journal.pone.0116794
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic and Temporal Partitioning of Cicada Assemblages in City and Mountain Environments

Abstract: Comparing adaptations to noisy city environments with those to natural mountain environments on the community level can provide significant insights that allow an understanding of the impact of anthropogenic noise on invertebrates that employ loud calling songs for mate attraction, especially when each species has its distinct song, as in the case of cicadas. In this study, we investigated the partitioning strategy of cicada assemblages in city and mountain environments by comparing the acoustic features and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 34 publications
(42 reference statements)
0
8
0
Order By: Relevance
“…Anthropogenic noise produced by human activities affects acoustic communication in the cicada Cryptotympana takasagona in the Kaohsiung metropolitan areas of southern Taiwan, which did not call more in noise gaps and acoustic features of its calling songs significantly increased with ambient noise levels 46 . However, it was also revealed that there was no significant temporal partitioning of cicada assemblages in either noisy city or natural mountain environments, and that for the common species found in both environments, the calling activity patterns at both seasonal and diel time scales were significantly consistent across sites and across environments 47 . Future exploration of whether the normal mating patterns or resource costs of obtaining mates of S .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Anthropogenic noise produced by human activities affects acoustic communication in the cicada Cryptotympana takasagona in the Kaohsiung metropolitan areas of southern Taiwan, which did not call more in noise gaps and acoustic features of its calling songs significantly increased with ambient noise levels 46 . However, it was also revealed that there was no significant temporal partitioning of cicada assemblages in either noisy city or natural mountain environments, and that for the common species found in both environments, the calling activity patterns at both seasonal and diel time scales were significantly consistent across sites and across environments 47 . Future exploration of whether the normal mating patterns or resource costs of obtaining mates of S .…”
Section: Discussionmentioning
confidence: 91%
“…The phonotaxis of S . yangi males also makes this species susceptible to negative impacts of anthropogenic sounds which might disrupt mating activity of this species 46 , 47 . Anthropogenic noise produced by human activities affects acoustic communication in the cicada Cryptotympana takasagona in the Kaohsiung metropolitan areas of southern Taiwan, which did not call more in noise gaps and acoustic features of its calling songs significantly increased with ambient noise levels 46 .…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have suggested that it is unlikely that invertebrates will be able to temporally shift calling because there are increased costs to calling at other times of day, owing to suboptimal atmospheric conditions, particularly at sunset (Van Staaden and Römer, 1997). In addition, short-term temporal activities for some invertebrates might be constrained by phylogenetic history (Shieh et al, 2015). Third, like some vertebrates, invertebrates could increase the amplitude of their calls (Lombard effect) (Nemeth and Brumm, 2010).…”
Section: Strategies To Avoid Maskingmentioning
confidence: 99%
“…Divergence of signal properties reduces masking, enables segregation of competing sound streams (MacDougall-Shackleton et al, 1998;Krishnan, 2019b), and thus reinforces species recognition and premating isolation between close relatives (Nelson, 1988(Nelson, , 1989Grant and Grant, 1996;Qvarnström et al, 2006). In diverse animals [crickets: (Schmidt et al, 2013), cicadas: (Shieh et al, 2015), aquatic insects: (Gottesman et al, 2020), fish: (Ruppé et al, 2015;Bertucci et al, 2020), anurans: (Drewry and Rand, 1983;Duellman and Pyles, 1983;Narins, 1995;Chek et al, 2003), birds: (Kirschel et al, 2009b(Kirschel et al, , 2020Krishnan and Tamma, 2016;Chitnis et al, 2020), bats: (Heller and von Helversen, 1989;Kingston et al, 2000;Luo et al, 2019), primates: (Braune et al, 2008)], closely related sympatric species exhibit divergent signals, partitioning the acoustic resource to minimize acoustic competition. Each species is therefore predicted to occupy a unique region or "niche" in the acoustic resource, a hypothesis extrapolated from ecological niche theory (Hutchinson, 1957;Holt, 2009).…”
Section: Conceptual Foundationsmentioning
confidence: 99%